Strategi Manajemen Komunikasi Media Online PT. Warta Global Republik Dalam Mengatasi Persaingan Antarmedia Online - Usman, Isbat; L Nata, Andrian Anwar; Irawan, Hengki (STIES ALIFA, 2023)
The rapid growth of the internet has resulted in the widespread existence of online media in Indonesia. As a result, competition between these online media platforms is increasing. With so much competition between online media, this research was conducted to find out how the communication management strategy carried out by PT Warta Global Republik as a new online media company to overcome competition between other online media. The method applied in this research uses a qualitative approach by analyzing POAC communication management theory (Planning, Organizing, Actuating, and Controlling). The data collection techniques implemented involved documentation studies, literature studies, observation, and in-depth interviews. The results of this study show that the management strategy implemented by PT Warta Global Republik has a good and effective communication foundation. Starting from the planning stage, Warta Global Republik takes steps to evaluate previous performance results, then maintains what is good and then replaces what is ineffective. At the organizing stage Warta Global uses a communication approach with the Journalist Organization, then at the actuating stage Warta Global uses effective communication to move the team, finally at the controlling stage the Chief Editor of Warta Global as the Warta Network oversees all articles to comply with company regulations. From the analysis of POAC management theory, it can be seen that the results of research on Warta Global Republik's management strategy say that Planning, Organizing, Actuating and Controlling are important points in the communication management of a company. In addition, the editor-in-chief of Warta Global Republik also holds full responsibility for competing with competing online media